Analisis faktor pembangunan desa dalam pengembangan desa mandiri berkelanjutan pada Desa Bunghu Aceh Besar - Lisnawati, Lisnawati; Lestari, Soraya (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
The independence of the village becomes a benchmark in economic development. An independent village is a village that can produce products and works originating from the village's natural and human resources. But this is certainly not easy. There are still many villages in Aceh that have not been able to manage natural resources because of limited human resources. As the village of Bunghu, the people in the rural areas are still unable to make maximum use of resources. Thus, it is necessary to innovate and collaborate on the processing of natural resources. Therefore village officials are expected to be able to manage village funds by the Law. The purpose of this study is to analyze the factors of sustainable independent village development and development in the village of Bunghu. This research was conducted with an explanatory descriptive method by looking at planning, implementation, and accountability as a general factor of sustainable village development. Research data collection was carried out using interviews and questionnaires. The output in this study is to help plan the implementation of work programs (strengthening human resources), the use of technology in improving the quality of performance (digitalization), and economic improvement with the establishment of the Village SMEs. So that this research was carried out with the achievement level of a prototype demonstration of the village government system in the rural environment by looking at the application or application of village laws in planning, implementation and accountability procedures.DOI:Â  https://doi.org/10.26905/pjiap.v4i2.3390